Ilmu Prosodi Dalam Komunikasi Guru Pendidikan Anak Usia Dini - Yasa, I Made Ardika; Agung, Anak Agung Gde; Sulindawati, Ni Luh Gede Erni (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
This article discusses the importance of prosody in the communication of early childhood education teachers. Prosody involves the appropriate use of intonation, rhythm, and speech tempo to enhance language comprehension, speaking skills, and children's engagement in learning. The article explains the positive impacts of utilizing prosody in children's learning, including better language comprehension, smoother speaking skills, improved understanding of meaning, increased engagement and motivation, and the development of social-emotional skills. Challenges in the use of prosody are also addressed, such as limited awareness and practical skills in regulating intonation and speech rhythm. However, the article also provides strategies to overcome these challenges, such as training and professional development, collaboration, reflection, the use of technology, and feedback. The implications for the professional development of teachers in prosody are also discussed, including training, collaboration, the use of technology, observation, and the formation of learning communities. This article provides an in-depth understanding of the role and benefits of prosody in the communication of early childhood education teachers, as well as practical guidance for teachers' professional development in mastering prosody.